Semi-renovationism in the Russia Orthodox Church in the middle of 1920-s.: toward the question about the church policy’s estimate of bishop Irenaeus (Shulgin) of Elabuga and bishop Alexiy (Kuznetsov) of Sarapulsk - Zimina Nina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article concerns the activity of the St. Petersburg Department of the Moscow Society for Religious education, targeted to give the western Christians the knowledge about the affairs’ state of the Eastern Church. The author identifies the literature published and translated by Russian theologians and members of clergy for western Christians from 1871 to 1880. She describes the work’s methods of the Department. The response of western theologians was the publication of works about the Eastern Church. Members of the St. Petersburg Department managed to fulfill designated tasks despite the short period of activity. They illuminated as much as possible the state of the contemporary Church, a church history and theology and assisted western and east Christians in the dialog’s development.